Immunovirological status in people with perinatal and adult-acquired HIV-1 infection: a multi-cohort analysis from FranceResearch in context - Rémonie Seng; Pierre Frange; Albert Faye; Catherine Dollfus; Jérôme le Chenadec; Faroudy Boufassa; Asma Essat; Tessa Goetghebuer; Elisa Arezes; Véronique Avettand-Fènoël; Jean-Joël Bigna; Stéphane Blanche; et al. (The Lancet Regional Health. Europe, 2024)
Summary: Background: No study has compared the virological and immunological status of young people with perinatally-acquired HIV infection (P-HIV) with that of people with HIV adulthood (A-HIV) having a similar duration of infection. Methods: 5 French cohorts of P-HIV and A-HIV patients with a known date of HIV-infection and receiving antiretroviral treatment (ART), were used to compare the following proportions of: virological failure (VF) defined as plasma HIV RNA ≥ 50 copies/mL, CD4 cell percentages and CD4:CD8 ratios, at the time of the most recent visit since 2012. The analysis was stratified on time since infection, and multivariate models were adjusted for demographics and treatment history. Findings: 310 P-HIV were compared to 1515 A-HIV (median current ages 20.9 [IQR:14.4–25.5] and 45.9 [IQR:37.9–53.5] respectively). VF at the time of the most recent evaluation was significantly higher among P-HIV (22.6%, 69/306) than A-HIV (3.3%, 50/1514); p ≤ 0.0001. The risk of VF was particularly high among the youngest children (2–5 years), adolescents (13–17 years) and young adults (18–24 years), compared to A-HIV with a similar duration of infection: adjusted Odds-Ratio (aOR) 7.0 [95% CI: 1.7; 30.0], 11.4 [4.2; 31.2] and 3.3 [1.0; 10.8] respectively. The level of CD4 cell percentages did not differ between P-HIV and A-HIV. P-HIV aged 6–12 and 13–17 were more likely than A-HIV to have a CD4:CD8 ratio ≥ 1: 84.1% vs. 58.8% (aOR = 3.5 [1.5; 8.3]), and 60.9% vs. 54.7% (aOR = 1.9 [0.9; 4.2]) respectively. Interpretation: P-HIV were at a higher risk of VF than A-HIV with a similar duration of infection, even after adjusting for treatment history, whereas they were not at a higher risk of immunological impairment. Exposure to viral replication among young patients living with HIV since birth or a very early age, probably because of lower adherence, could have an impact on health, raising major concerns about the selection of resistance mutations and the risk of HIV transmission. Funding: Inserm - ANRS MIE.